Work stress and well‐being in oncology settings: a multidisciplinary study of health care professionals. Issue 1 (28th September 2011) - Jones, Martyn C.; Wells, Mary; Gao, Chuan; Cassidy, Bernadette; Davie, Jackie
Abstract Objectives Staff working in oncology report high levels of work‐related stress. This arises partly from the nature of clinical work, including practitioner perceptions of high demand and low control or high effort and low reward. This comparative study investigated the correlates of work stress in a multidisciplinary group of staff and the associations between staff perceptions of the work environment, emotional distress, job satisfaction and work‐based social support. Methods This questionnaire study combined quantitative and qualitative assessment in a cohort sample of multidisciplinary staff (N = 85) working in a cancer centre in North East Scotland. Ethical approval was granted by the local Research Ethics Committee. This paper reports on the quantitative element of the study, Results Response rate was 50.6% (N = 85). Older, female and nursing and support staff were more likely to participate. Support staff reported the lowest perceptions of control, job satisfaction and managerial support. Radiographers reported the highest levels of job satisfaction, co‐worker and managerial support. Nurses perceived lower decision control and job satisfaction than allied health professionals or doctors. In general, perceptions of decisional control and reward were protective of job satisfaction, particularly when work demands were high. Co‐worker support was associated with perceptions of reduced effort, greater reward and increased satisfaction. Managerial support was also associated with greater control beliefs. Overall, sickness absence exceeded the 5% rates seen in other National Health Service surveys, whereas turnover intention rates were similar. Conclusion The development and introduction of multilevel strategies to reduce demand, improve control and support perceptions are warranted, particularly for support staff. Copyright © 2011 John Wiley & Sons, Ltd.